FORMULASI DAN EFEKTIFITAS SAMPO EKSTRAK BUAH PEDADA (Sonneratia caseolaris L) SEBAGAI ANTIKETOMBE TERHADAP Candida albicans - Sambodo, Dwi Kurniawati; Yani, Lisa Erie (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2020)
Half of the world's population has been affected by dandruff, especially those aged 15 to 50 years. Dandruff is one of the problems on the scalp with common symptoms of scales (exfoliation of dead skin), itching of the scalp and redness around the scalp. Dandruff can be caused by an oily scalp, hormones or fungus. One of the fungi that cause dandruff is Candida albicans. Based on research that has been done, secondary metabolite compounds of methanol extract of peada fruit peel which is a pure white compound in the form of powder are identified as alkaloid compounds. In general, alkaloids can be used as an antifungal. Anti-dandruff shampoo is a dosage that is often used daily and can be used to treat and prevent scalp from excessive dandruff where this shampoo contains active antifungal agents which are effective as an anti-dandruff. Pedada fruit was extracted using multilevel maceration method with methanol as a solvent. Pedada fruit extract shampoo is formulated with variations in extract concentration into 3 formulas. Shampoo was tested for physical properties and effectiveness of anti-dandruff using the Kirby-Bauer Diffusion method with PDA media. From the results obtained it can be concluded that the physical properties of the three formulas of pedada fruit extract shampoo (Sonnerratia caseolaris L) include organoleptic, pH , high foam , cycling test, and viscosity produced good physical properties in accordance with the standard test of the physical properties of shampoo, however Homogeneity test results show that formula III shampoo is less homogeneous. All three shampoo formulas are effective as anti-dandruff against the fungus Candida albicans.